(untitled) (Iter, 2022)
Can Greek concept of Beauty inelude dece i t and death? To answer this question. the author analices some aspeets of Afrodite s myth and Pandora ’s myth. Both myths shows the relation between Beauty. pie asure, death and deceit. Finally the text asserts that like a mirror the human body. young and beautiful human body. reflects the shine of divine Beauty. even its ambiguity shine-dark. life-death. pleasure-hurt.